A administraç\~ao pública deliberativa: Inteligência coletiva e inovaç\~ao institucional a serviço do público - Daniel Tarragó; Quim Brugué; José Celso Cardoso Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– A Deliberative Public Administration is a political commitment to progressive and progressive transformation of public administration, especially in countries like Brazil, whose accumulated experiments of citizen participation has excelled around the world. Therefore, it is argued in favor of social participation as a method of government, seeking to defuse some of the propositions often used to minimize or even ridicule the social participation in government processes. Additionally, the need to reinvent democracy defends itself, warning of the bankruptcy of the traditional ways of doing politics and, consequently, the inability of the current government to govern, and citizens to govern their own governments. Hence the need to regain good policy as a way to overcome the moral barbarism that took account of political relations and the government itself in Brazil and worldwide. Finally, it is to develop new administrative capabilities so that governments are able to better communicate your plans, goals and objectives, both internally, as in society. Therefore, the text establishes the reasons for the proposed new governance of public affairs: i) less specialization and more creativity; ii) less data and more philosophy; iii) less inbreeding and further diversity. In short, betting on relational skills (of technopolitical nature) of new generations of leaders and public servants in training, but also in institutional learning capacity due to both the collective intelligence already installed in our public offices as of participatory and deliberative practices already in use inside the same.
Keywords: H8; H80; 330; deliberative public administration; republic; democracy; development